(untitled) (Research, Society and Development, 2025)
Adverse situations send signals to the body, which in turn produce stressful stimuli. This process is defined as stress, and when it occurs frequently, it can trigger pathologies, since the continuous release of hormones represents an aggravating factor for the organism. This scenario is especially worrying in universities, where the individual must deal with several everyday situations. This article aims to relate, based on findings from the literature, stress and the immune system in university students. This is a systematic review that, through health descriptors, selected the terms: academic environment, immune system and physiological stress. Based on the PICO strategy, the research question was elaborated and the search term was defined. A total of 1,114 articles were identified in the databases, 551 publications were excluded, of which exceeded the period of 5 years and 1 duplicate publication. After analyzing the title, abstract and reading the full text, 7 articles were analyzed. According to the authors, students suffer from the changes and high demands of university life, leaving them increasingly exhausted, impacting their physical and psychological well-being. In short, there is a possible effect of stress on the immune system of university students, caused by various stressful events.